Adubação da cultura da soja baseada nos teores mínimos de fósforo e potássio no solo - Milanesi, Júnior Henrique (2015)
The soybean crop is of great importance for Brazilian agriculture, ensuring unquestionable relevance of the country, both as a producer, as an exporter of the grain. In this context, shows the precision agriculture, the main premise the management of variability found in field. This search for efficiency results in better productivity results, through a new strategy of farm management. Soil analysis in precision agriculture is georeferenced, attributing results to a specific crop location, which allows viewing of the variability of soil attributes through thematic maps. This work aimed to evaluate the soybean yield from the fixed-rate fertilization of an agricultural field, based on the minimum values for phosphorus (P) and potassium (K) in the soil analysis of the layer 0-0,10 m deep. Seeking to productivity 3.000 kg ha-1, the recommendation was 395 kg ha-1 of fertilizer in the formulation 2-23-23. A yield map was generated and this was compared with the soil chemical properties. The results indicated a yield range and the overall average well below expectations. These results were attributed to adverse environmental conditions (water stress and high temperatures), suffered by culture.